THE EFFECTIVENESS OF USING VIDEO CLIP IN TEACHING SPEAKING TO DELIVER HORTATORY EXPOSITION TEXT: An Experimental Research - Susanti, Sandra; Amin, Bahrun; Maharida (Journal of Computer Interaction in Education, 2018)
This This research aimed at finding out whether or not the use of Video Clip and Hortatory Exposition Text effective in improving student’s pronunciation and student’s vocabulary. The researcher used an experimental research. The research had conducted a treatment, where the class consisted of six meetings. The location of this research was done at the second grade students of SMA N 22 Makassar with 30 students and stand by one class using individual test in pre-test, treatments and post-test design.The research instrument was an oral presentation as a pre-test and posttest. In pre-test the students presented their argument after they watched the video clip that given by cell phone and they were explained based on the structural of hortatory exposition text. The findings indicated that the use of video clip as media in the teaching speaking to deliver hortatory exposition text was effective in term of pronunciation and vocabulary. It is provided by the pre-test is (59, 75) and compare to the mean score of post-test is 72, 84 and the percentages of the improvement is 21, 90